Time series of autonomous phase-sensitive radar (ApRES) measurements and determined basal melt rates at location EIS8 on Ekström Ice Shelf, Antarctica from January 2021 to November 2021 - Ole Zeising; Daniel Steinhage; Sophie Berger; Reinhard Drews; M Reza Ershadi; Tanja Fromm; Tore Hattermann; Frank Pattyn; Olaf Eisen (PANGAEA, 2025)
The dataset consists of raw data and derived melt rates from autonomous phase-sensitive radar (ApRES) measurements. The ApRES was operated with two broadband frame antennas at the Ekström Ice Shelf since April 2020 with one measurement every hour. These Lagrangian measurements allow the estimation of basal melt rates based on estimated vertical displacements of englacial and basal reflections. The ApRES is an autonomous operating frequency-modulated continuous wave (FMCW) radar that transmits a tone sweep - called chirp - ranging from 200 to 400 MHz over a period of one second. In order to improve the signal-to-noise ratio, 20 chirps were transmitted within a single measurement. These measurements were repeated every hour. A raw data file contains up to 4 measurements. Background of the pRES-system is published by Nicholls et al. (2015). The processing of the data is described in Zeising et al. (2025). The estimated basal melt rates are based on the analysis of firn densification, strain thinning, and the change in ice thickness from the determination of vertical displacements. The basal melt rates are averaged over 7 days (moving window). To represent the variability of the melt rate on sub-weekly timescales, we also calculated the 7 day standard deviation of the basal melt rates based on a 1 day moving window. The uncertainty of the basal melt rate is based on the uncertainty of the strain estimation and the determination of the ice thickness change. Data are exported in 4 hour intervals. A positive melt rate represents melting. Details on the processing are given in Zeising et al. (2025). The time series contains a data gap from 1 April to 16 May 2021.